EFEKTIVITAS KONSELING KELOMPOK PENDEKATAN COGNITIVE BEHAVIOR THERAPY TERHADAP PERILAKU SIBLING RIVALRY SISWA SD NEGERI 3 SILIRAGUNG - Oky Faresa Ayu Kariyany; Heribertus Wicaksono; Raup Padillah (BIMBINGAN DAN KONSELING BANYUWANGI, 2022)
The purpose of this research is to measure the effectiveness of using group counseling approach to Cognitive Behavior Therapy to reduce Sibling Rivalry behavior of students at SDN 3 Siliragung.The method in this research is descriptive using a quantitative approach. The variables in this study were group counseling with Cognitive Behavior Therapy and Sibling Rivalry approaches. Respondents in this study were 10 students who indicated experiencing Sibling Rivalry symptoms from the observations that had been made. Methods of data collection using the results of observations, questionnaires and interviews. The data processing technique uses the SPSS application. Based on the results of data analysis of research conducted at the State Elementary School 3 Siliragung on students "Group Counseling with the CBT (Cognitive Behavior Therapy) approach is effective for overcoming sibling rivalry in students of SD Negeri 3 Siliragung" with the results of data calculations (22.24> 2.074) therefore because H0 is rejected, Ha is accepted. The results of this study can be a recommendation for counselors when dealing with clients with sibling rivalry problems that are often experienced by elementary school children who are categorized as early childhood, to reduce the potential for sibling rivalry to occur by providing group counseling guidance services with a CBT (Cognitive Behavioral) approach. therapy).